Direct AMPK Activation Corrects NASH in Rodents Through Metabolic Effects and Direct Action on Inflammation and Fibrogenesis. Issue 1 (7th September 2021) - Gluais‐Dagorn, Pascale; Foretz, Marc; Steinberg, Gregory R.; Batchuluun, Battsetseg; Zawistowska‐Deniziak, Anna; Lambooij, Joost M.; Guigas, Bruno; Carling, David; Monternier, Pierre‐Axel; Moller, David E.; Bolze, Sebastien; Hallakou‐Bozec, Sophie
Abstract : No approved therapies are available for nonalcoholic steatohepatitis (NASH). Adenosine monophosphate–activated protein kinase (AMPK) is a central regulator of cell metabolism; its activation has been suggested as a therapeutic approach to NASH. Here we aimed to fully characterize the potential for direct AMPK activation in preclinical models and to determine mechanisms that could contribute to efficacy for this disease. A novel small‐molecule direct AMPK activator, PXL770, was used. Enzyme activity was measured with recombinant complexes. De novo lipogenesis (DNL) was quantitated in vivo and in mouse and human primary hepatocytes. Metabolic efficacy was assessed in ob / ob and high‐fat diet–fed mice. Liver histology, biochemical measures, and immune cell profiling were assessed in diet‐induced NASH mice. Direct effects on inflammation and fibrogenesis were assessed using primary mouse and human hepatic stellate cells, mouse adipose tissue explants, and human immune cells. PXL770 directly activated AMPK in vitro and reduced DNL in primary hepatocytes. In rodent models with metabolic syndrome, PXL770 improved glycemia, dyslipidemia, and insulin resistance. In mice with NASH, PXL770 reduced hepatic steatosis, ballooning, inflammation, and fibrogenesis. PXL770 exhibited direct inhibitory effects on pro‐inflammatory cytokine production and activation of primary hepatic stellate cells. Conclusion: In rodent models, direct activation of AMPK is sufficient to produce improvements in all core components of NASH and to ameliorate related hyperglycemia, dyslipidemia, and systemic inflammation. Novel properties of direct AMPK activation were also unveiled: improved insulin resistance and direct suppression of inflammation and fibrogenesis. Given effects also documented in human cells (reduced DNL, suppression of inflammation and stellate cell activation), these studies support the potential for direct AMPK activation to effectively treat patients with NASH. Abstract : AMPK is a key cellular sensor that is activated in response to a variety of conditions that deplete energy levels. AMPK activity is reduced in NASH. Direct AMPK activation using PXL770, a clinical‐stage investigational drug, improves the hallmarks of NASH and type 2 diabetes in rodent models.